The role of myeloid-derived suppressor cells in children - Brauner, Jordan; Wilt, Anna; Montgomery, Christopher P.; Bline, Katherine (Frontiers in Pediatrics, 2025)
Myeloid-derived suppressor cells (MDSC) were first recognized over twenty years ago as a key immunomodulatory cell population. Since their initial identification, a growing body of literature points to the importance of MDSC as a heterogeneous, immunosuppressive cell population and as a therapeutic target in adults with cancer. MDSC are potent suppressors of T cells and Natural Killer (NK) cells and can be helpful or harmful to the host depending on the pathophysiology. For example, MDSC are beneficial in pregnancy and prevent spontaneous abortion by promoting maternal-fetal tolerance. Increased MDSC are also associated with improved outcomes in patients with graft vs. host disease by decreasing T cell-driven inflammation. However, MDSC can also be harmful and are known to be pathologic in adults with cancer and chronic infections by promoting tumor escape and impairing pathogen clearance, respectively. Despite the widespread recognition of the importance of MDSC and their immune suppression effects in adults, much less is known regarding the role of MDSC in children. Research investigating MDSC in children lags significantly behind adult studies. In fact, while over 5,000 publications on PubMed discuss MDSC in immune regulation, fewer than 50 of these publications focus specifically on their role in children. This review aims to summarize the existing literature on the role of MDSC in children and identify important directions for future research, including targeting these cells in the pediatric population to improve clinical outcomes.